2015
DOI: 10.1155/2015/971982
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Toxicity, Cytochrome P450 Enzyme Inhibition, and hERG Channel Blockade Studies with a Polyherbal, Ayurvedic Formulation for Inflammation

Abstract: Ayurvedic plants are known for thousands of years to have anti-inflammatory and antiarthritic effect. We have recently shown that BV-9238, a proprietary formulation of Withania somnifera, Boswellia serrata, Zingiber officinale, and Curcuma longa, inhibits LPS-induced TNF-alpha and nitric oxide production from mouse macrophage and reduces inflammation in different animal models. To evaluate the safety parameters of BV-9238, we conducted a cytotoxicity study in RAW 264.7 cells (0.005–1 mg/mL) by MTT/formazan met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…Moreover, in silico analysis showed that the withaferin A interacts with cytochrome P450 enzymes through hydrogen bonds with specific sites, which might affect its interactions with bromobenzene. This study suggests the hepatoprotective and nephroprotective effects of withaferin A against bromobenzene-induced toxicity, which might be due to inhibition of the activity of CYPs, which are crucial in the bio-activation of bromobenzene (Dey et al 2015). The protective effect of withaferin A can be hypothesized by relating the above parameters.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Moreover, in silico analysis showed that the withaferin A interacts with cytochrome P450 enzymes through hydrogen bonds with specific sites, which might affect its interactions with bromobenzene. This study suggests the hepatoprotective and nephroprotective effects of withaferin A against bromobenzene-induced toxicity, which might be due to inhibition of the activity of CYPs, which are crucial in the bio-activation of bromobenzene (Dey et al 2015). The protective effect of withaferin A can be hypothesized by relating the above parameters.…”
Section: Discussionmentioning
confidence: 77%
“…Withaferin A (WA), a steroidal lactone found in the leaves and roots of Withania somnifera, has been reported to possess anti-inflammatory, antiangiogenic, CYP-inhibiting, anti-proliferative, and anti-pyretic activities (Yokota et al 2006;Sabina et al 2008; Bargagna-Mohan et al 2010;Dey et al 2015). In a previous study, it has been demonstrated that W. somnifera has protective effects against bromobenzene-induced damage in rat liver and kidney mitochondria (Mahima et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Both Boswellia serrata and Equisetum arvense are mentioned in phytovigilance as possible modulators of cytochrome P450 action but the modulating action of these two medicinal plants seems strongly dose‐related. In 2006, Frank and Unger described Boswellia serrata as an inhibitor of numerous cytochrome P450 enzymes, while more recently, Dey, Chaskar, Athavale, and Chitre () when using Boswellia serrata in association with other medicinal plants, did not find such inhibitory activity and hypothesized that a particularly high dose of Boswellia extract is required to act on cytochrome P450 enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…[40] Prominently, BV-9238, a proprietary formulation of W. somnifera, B. serrata, Z. officinale, and Curcuma longa, inhibits LPS-induced TNF alpha and NO production from mouse macrophage and reduces inflammation in different animal models. BV-9238 is found potential, safe and well-tolerated anti-inflammatory formulation.…”
Section: Ayurvedic Medicinesmentioning
confidence: 99%
“…BV-9238 is found potential, safe and well-tolerated anti-inflammatory formulation. [40] Curcuma zedoaria (family Zingiberaceae) ethanolic rhizome extract shows anti-inflammatory activity. [41] Turmeric is an Ayurvedic medicine practiced for centuries for the treatment of inflammatory disorders including arthritis.…”
Section: Ayurvedic Medicinesmentioning
confidence: 99%